Sustainable Anatase Extracted from Beach Sands Generates 0.77 mW/cm2 Photovoltaic Power in Dye-Sensitized Solar Cells - Oishy Roy; Muhammad S. Bashar; Syed A. M. Tofail; Ehtsham U. Haq; Fahmida Gulshan (Energy Material Advances)
Beach and river sand deposits in Bangladesh can be a potential global source of sustainable extraction of nanocrystalline anatase used as electron transport layers in dye-sensitized solar cells (DSSCs). We demonstrate up to 0.77 mW/cm2 power density in DSSCs made with nanocrystalline anatase processed from a sustainable source of beach sands from Cox’s Bazar, Bangladesh. This anatase was produced using simple, and scalable, hydrometallurgical extraction of the nanocrystalline anatase form of titania (TiO2) from natural beach sand. An extensive range of physicochemical characterizations showed that we were able to produce nanocrystalline anatase of an average crystallite size of 8.6 to 11.6 nm and reasonable phase purity with the presence of carbon, nitrogen, sulfur, phosphorus, and silicon impurities. Screen-printed thick films made from these anatase particles showed a 2.90- to 2.95-eV bandgap for an indirect transition and a 3.06- to 3.13-eV bandgap for a direct transition, with the absorption edge lying in the range of 340 to 450 nm and the Urbach energy in the range of 0.62 to 0.97 eV. These properties compare fairly well with those of nanocrystalline anatase reported in the literature. Interestingly, we showed that the properties of the anatase extracted can be adjusted using hydrometallurgical parameters that affect the phase purity of the precursor extracted from the beach sands. Our investigation uncovers the potential of Cox’s Bazar beach sand as a potential global source of sustainable anatase for DSSCs and other photocatalytic applications.